Retinal development in albinism: a prospective study using optical coherence tomography in infants and young children. (26th February 2015) - Lee, Helena; Purohit, Ravi; Sheth, Viral; Papageorgiou, Eleni; Maconachie, Gail; McLean, Rebecca J; Patel, Aarti; Pilat, Anastasia; Anwar, Samira; Sarvanathan, Nagini; Proudlock, Frank A; Gottlob, Irene
Abstract: Background: Retinal development normally involves migration of the inner retinal layers away from the fovea, migration of the cone photoreceptors into the fovea, and elongation of the photoreceptors over time. This process is arrested prematurely in albinism. However, because retinal development continues at least until the age of 4 years, when development arrests in albinism is uncertain. In this study we outlined the time course of retinal development in children with albinism. Methods: We studied 44 children with a diagnosis of albinism and 223 control participants. All participants were aged between 0 and 6 years. We obtained 219 mixed cross-sectional and longitudinal optical coherence tomography examinations in the albinism group and compared them with 558 control examinations. Retinal layer segmentation was performed with ImageJ software. Generalised linear mixed regression modelling was used to analyse group differences in retinal development. Findings: In the albinism group, inner retinal layer migration from the fovea was delayed and arrested prematurely, resulting in a significantly thicker central macular thickness than in the control group (p<0·0001). Whereas the central macular thickness increased with age in the control group, in the albinism group it initially decreased with age as a result of continuing regression of the inner retinal layers (p=0·041). The perifoveal retinal thickness was significantly decreased in albinism from a reduction of both inner (p<0·0001) and outer (p<0·0001) retinal layer thicknesses. There was evidence that the photoreceptor layers across the fovea were elongating in albinism, albeit at a reduced rate, compared with the control group. This difference was most apparent for the foveal photoreceptor inner segment (p=0·001). Interpretation: Our findings show that perturbations exist in several aspects of retinal development including the migration and differentiation of the neuronal cells within the retina. We showed continuing regression of the inner retinal layers and elongation of the photoreceptor layers suggesting residual plasticity of the developing albino retina. This finding is important because treatment at the earliest stages of the condition might normalise retinal development and optimise vision. Funding: UK Medical Research Council (grant number MR/J004189/1 ), Ulverscroft Foundation, National Eye Research Centre, Nystagmus Network UK.